The Response of Goat Manure and Liquid Organic Fertilizer from Agricultural Waste to the Growth and Production of Okra (Abelmoschus esculentus L.) - Apri Yunus Jubilater Sitorus; Najla Lubis; Desi Sri Pasca Sari Sembiring (Sean Institute, 2026)
Okra is a plant that has many benefits and nutritional content contained in its fruit. The purpose of this study was to determine the response of goat manure and liquid organic fertilizer from agricultural waste on the growth and production of okra plants. This study used a Factorial Randomized Block Design (RAK) consisting of 2 treatment factors, 16 treatment combinations and 3 blocks so that the total number of plots was 48 research treatment plots. Factor I was goat manure (K) which consisted of 4 treatment levels, namely K0 = 0 g/plot, K1 = 600 g/plot, K2 = 1200 g/plot, and K3 = 1800 g/plot. Factor II was agricultural waste POC (L) which consisted of 4 treatment levels, namely L0 = 0 ml/liter of water/plot, L1 = 15 ml/liter of water/plot, L2 = 30 ml/liter of water/plot, and L3 = 45 ml/liter of water/plot. The results of the study with the provision of goat manure on the growth and production of okra plants provided a very significant response from all observation parameters. The best level was found in the K3 treatment. The application of agricultural waste POC to okra plant growth and production showed no significant response across all observed parameters. However, the number of leaves at 4 weeks post-planting showed a significant response. The best level was found in the L1 treatment.